2017
DOI: 10.1111/jdi.12612
|View full text |Cite
|
Sign up to set email alerts
|

Association between TCF7L2 polymorphisms and gestational diabetes mellitus: A meta‐analysis

Abstract: Aims/IntroductionStudies have been carried out to evaluate the correlation between TCF7L2 genetic polymorphisms and gestational diabetes mellitus (GDM) risk. However, the conclusions from these studies are incomplete, because partial single nucleotide polymorphisms (SNPs) were analyzed. We carried out a meta‐analysis aimed to systematically evaluate TCF7L2 gene polymorphisms and GDM susceptibility in all population and racial/ethnic subgroups to afford a foundation for future research.Materials and MethodsPubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…One of the strongest genetic predispositions for type 2 diabetes in humans is a variant of the Tcf7l2 gene [7]. Polymorphisms in Tcf7l2 have also been linked to body weight, triglyceride metabolism, and gestational diabetes [152], [153], [154]. In this study, we report that the Wnt-effector TCF7L2 is enriched in both human and mouse white adipose tissue and its expression is reduced in white adipose tissue of both genetic and diet-induced models of obesity.…”
Section: Discussionmentioning
confidence: 64%
“…One of the strongest genetic predispositions for type 2 diabetes in humans is a variant of the Tcf7l2 gene [7]. Polymorphisms in Tcf7l2 have also been linked to body weight, triglyceride metabolism, and gestational diabetes [152], [153], [154]. In this study, we report that the Wnt-effector TCF7L2 is enriched in both human and mouse white adipose tissue and its expression is reduced in white adipose tissue of both genetic and diet-induced models of obesity.…”
Section: Discussionmentioning
confidence: 64%
“…TCF7L2 , a transcription factor of the Wnt and Hippo signalling pathway, is hyper-methylated and up-regulated in PE, suggesting a possible positive relationship between the extent of m6A methylation and the transcript level. Earlier findings revealed that a TCF7L2 variant increased the risk of incident hypertension or diabetes mellitus ( Bonnet et al, 2013 ; Chang et al, 2017 ); however, the relationship between TCF7L2 and PE is not clear. To provide further insight, it will be necessary, in a future study, to elucidate the biological function of TCF7L2 in the context of PE.…”
Section: Discussionmentioning
confidence: 97%
“…According to the literature, a higher risk of DM is indicated by TCF7L2 SNP rs7901695 C allele [21]. CC and CT alleles were combined into one group.…”
Section: 3mentioning
confidence: 99%
“…TCF7L2 SNP rs7903146 the risk allele for DM is T [21], so we have combined CT and TT alleles into one group. The difference between the GDM and the general population groups remained statistically significant (p = 0.008).…”
Section: 3mentioning
confidence: 99%